2017
DOI: 10.1002/app.45164
|View full text |Cite
|
Sign up to set email alerts
|

Compatibilized TPU‐PDMS blends: Pros and cons of melt mixing and solution mixing techniques

Abstract: The present work describes the influence of processing route on thermomechanical properties of thermoplastic polyurethane (TPU) and polydimethylsiloxane (PDMS) compatibilized blends. In this study, compatibilized blends of TPU and PDMS prepared by melt mixing and solution mixing techniques were compared. Ethylene methyl acrylate at different doses of 1, 2, 3, and 4 phr was used as the compatibilizer in 90:10, 80:20, and 70:30 blend ratios of TPU and PDMS. Optimum percentage of compatibilizer was same in both t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…However, compared with SR/EVM blend, the lower tan δ value of the compatibilized composites with different loading of silane‐modified MS whisker (5 and 20 phr) is ascribed to rubber‐filler interaction, which inhibits the mobility of polymer chains. The interaction of fillers and rubber inhibits the movement of the polymer chains, resulting in a decrease in tan δ max or an increase in T g 29 . Similar findings have been reported by other groups 11,30,31 …”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…However, compared with SR/EVM blend, the lower tan δ value of the compatibilized composites with different loading of silane‐modified MS whisker (5 and 20 phr) is ascribed to rubber‐filler interaction, which inhibits the mobility of polymer chains. The interaction of fillers and rubber inhibits the movement of the polymer chains, resulting in a decrease in tan δ max or an increase in T g 29 . Similar findings have been reported by other groups 11,30,31 …”
Section: Resultssupporting
confidence: 85%
“…The interaction of fillers and rubber inhibits the movement of the polymer chains, resulting in a decrease in tan δ max or an increase in T g . 29 Similar findings have been reported by other groups. 11,30,31…”
Section: Dynamic Mechanical Propertiessupporting
confidence: 87%
“…Many of the mechanical characterizations have shown that simple linear elastic model is sufficient and the need for more generalized models like Mooney–Rivlin should be invoked only on special occasions. Being a thermoplastic elastomer, the temperature dependency on the crosslinking process is crucial in dictating the final mechanical properties, especially the elastic modulus ( E ) of the material . This is particularly important during microfabrication as the thermodynamics of curing can give rise to issues while performing the soft lithography especially to fabricate structures of the order of nanometer dimensions .…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, even at such low concentrations, the inclusion of PDMS was shown to improve chemical stability and wear resistance. Nando and co-workers had also devised the reactive compatibilization of TPU and PDMS using ethylene-methyl acrylate (EMA). , EMA was initially grafted onto PDMS. During the subsequent melt-mixing with TPU, it facilitated specific interactions through hydrogen bonding between its >CO and the unassociated >NH– of the urethane group.…”
Section: Introductionmentioning
confidence: 99%